ПРОКУРОРСКИЙ НАДЗОР ЗА СОБЛЮДЕНИЕМ ПРАВ, СВОБОД И ЗАКОННЫХ ИНТЕРЕСОВ ЛИЦА ПРИ ПРОВЕДЕНИИ ОБЫСКА: ВОПРОСЫ ТЕОРИИ И ПРАКТИКИ - Левин, Виталий Игоревич (SUPREMANCE OF LAW, 2018)
The article examines the issues of prosecutor’s supervision over observance of the rights, freedoms and legal interests of the person during the search. The specifics of the prosecutor’s implementation of his powers to ensure the rights and freedoms of the individual, regarding which the search is conducted. The study of the issue under investigation was carried out taking into account three main stages: preliminary, judicial and execution of the decision of the investigating judge on the permission to search a home or other possession.